Pengaruh Pembelajaran Elektronik (E-Learning) Terhadap Mutu Belajar Mahasiswa Program Studi Pendidikan Ekonomi - Windy Utami Putri; Rinto Alexandro; Meli Wulandari (Edunomics Journal, 2021)
This research was conducted to determine the influence of electronic learning on the quality of learning of students of the Economic Education Study Program of FKIP University of Palangka Raya. This study uses quantitative method, samples are taken using total sampling technique so that the number of samples is equal to the population. Data collection techniques by disseminating questionnaires on Google Form. Data analysis using simple linear regression analysis. Based on the results of the study found that electronic learning has a positive and significant influence on the quality of learning of students economic education program is shown by the significance of the influence of e-learning learning of 0.000 < 0.05 and the value of Fhitung > Ftabel (21,466 > 4.04) means Ha accepted and Ho rejected. Based on the results of a simple linear regression test produced Y = 12,492 + 0.834X with a coefficient of determination of 0.309 which means that e-learning has an influence of 30.9% on the quality of student learning, while 69.1% is influenced by other factors.